2021
DOI: 10.3389/fphar.2021.733475
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sacubitril/Valsartan on Clinical and Echocardiographic Parameters in Heart Failure Patients With Reduced Ejection Fraction: Data From a Real Life 2-year Follow-Up Study

Abstract: Heart failure (HF) represents a widespread health problem characterized by high morbidity and mortality. Sacubitril/Valsartan (sac/val) has improved clinical prognosis in patients affected by HF with reduced ejection fraction (HFrEF). The aim of this study was to evaluate the effectiveness and durability of sac/val treatment on the clinical, hemodynamic and echocardiographic parameters, in real-life consecutive HFrEF outpatients, evaluated up to 2-years of follow-up. We collected 300 repeated observations over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 37 publications
7
9
0
Order By: Relevance
“…In this longitudinal-observational, single-center study, considering 90 HFrEF patients with optimal medical therapy but still symptomatic, sac/val treatment demonstrated efficacy, safety and durability every 6 months up to 30 months of follow-up, with an important improvement in clinical and echocardiographic parameters confirming previous evidence ( Armentaro et al, 2021 ). Notably, sac/val showed also a significant betterment in renal function, glycometabolic state and insulin sensitivity parameters and this effect was particularly noticeable in T2DM patients who represented about 67% of the entire population.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In this longitudinal-observational, single-center study, considering 90 HFrEF patients with optimal medical therapy but still symptomatic, sac/val treatment demonstrated efficacy, safety and durability every 6 months up to 30 months of follow-up, with an important improvement in clinical and echocardiographic parameters confirming previous evidence ( Armentaro et al, 2021 ). Notably, sac/val showed also a significant betterment in renal function, glycometabolic state and insulin sensitivity parameters and this effect was particularly noticeable in T2DM patients who represented about 67% of the entire population.…”
Section: Discussionsupporting
confidence: 83%
“…A secondary analysis of the PARADIGM-HF trial has shown a beneficial effects of sac/val on renal function with patients treated with sac/val exhibiting lower decline in renal function than those treated with enalapril, an improvement that was more pronounced in diabetic patients compared to non-diabetics ( Packer et al, 2018 ). Accordingly, a 24-month follow-up real-life study has demonstrated the efficacy and durability of sac/val treatment in patients with HFrEF not only in terms of clinical, haemodynamic and echocardiographic parameters but also regarding the renal function ( Armentaro et al, 2021 ). Data on the improvement of metabolic parameters with sac/val treatment, in particular in diabetic patients, derive mainly from post-hoc analysis of the large clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we observed a significant reduction of sPAP after start of S/V therapy. A similar finding was reported from other observational studies [ 6 , 35 , 37 , 39 , 40 ].…”
Section: Discussionsupporting
confidence: 91%
“…Thus, results may not be transferable to patients with stable chronic HFrEF. A recent observational study of 60 outpatients with HFrEF reported a significant increase in cardiac index as determined by echocardiography after up to 2 years of S/V treatment [ 40 ]. However, as the first follow-up assessment of cardiac index was performed 6 months after therapy initiation, the study does not provide any data on short-term haemodynamic effects of S/V.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies ( 37 – 40 ), in our patients, we also observed that treatment with sac/val significantly improve left ventricular (LV) remodeling and function parameters. Sac/val treatment was associated with a reduction in LAV and end-systolic and end-diastolic LV volumes; together with this, also diastolic function parameters were improved, with an E/A ratio increase and E/e′ reduction, thus showing a lowering of intraventricular filling pressure.…”
Section: Discussionsupporting
confidence: 86%